Trends of Modern Russian Criminal Policy in the Russian Federation - EFREMOVA, Marina Alexandrovna; ROGOVA, Evgenia Viktorovna; KLEBANOV, Lev Romanovich; GORSHENIN, Alexander Alexandrovich; PARKHOMENKO, Dmitry Alexandrovich (Journal of Advanced Research in Law and Economics, 2019)
The article is devoted to the study of the trends in Russian criminal policy at the present stage of its development. The authors come to the conclusion that criminal policy today is understood and exists in three aspects: first, as a policy in its own (narrow) sense of the word, that is, state political activity in the field of combating crime; second, as law enforcement in this area (practical policy); third, as a branch of scientific knowledge of complex content (based on the connection of criminal law, process, criminal executive law, criminology with political science, sociology, management theory), the so-called criminal political science. Criminal policy, implemented at different stages of development of social relations, is characterized by certain priority areas. Currently, with regard to international documents and standards, one of the key trends in Russian criminal policy is humanization, as evidenced by the analysis of changes and additions to the criminal law over the past twenty years.